Assessing the viability of Tenera oil palm shells as fine and coarse aggregates in structural lightweight concrete: microstructure and mechanical properties - Hama, Mohammed Fadhil (2024)
Oil palm shells (OPS), a significant waste product of the oil palm industry, have raised environmental concerns due to their abundance and disposal challenges. Researchers have explored the potential use of OPS as coarse aggregates in structural lightweight concrete (SLWC) to address these issues. However, most studies lack specific OPS variety information, although indications by the thickness and accompanying figures point to the prevalent use of Dura OPS. The emergence of Tenera, a hybrid oil palm variety with thinner OPS, has significant implications, as it offers a 57% reduction in OPS thickness and a 30% increase in palm oil production compared to Dura OPS. Over 90% of oil palm farmers in Malaysia have already switched to the Tenera fruit, suggesting that the Dura variety may be phased out in the future.